Approach to hernial defect in laparoscopic incisional hernia repair - N. A., Nijas; Koppad, Sanjay N. (International Surgery Journal, 2018)
Background: Ventral hernias are the second most common type of abdominal hernias and account for approximately 10% of all hernias. Recurrence rates after open suture repair have been reported to be as high as 31% to 49%. Laparoscopic ventral hernia repair (LVHR) has been reported to have reduced recurrence rates as compared to open mesh repair, reduced infection rate, shorter recovery time and hospital stay. During LVHR, closure of the hernial defect is a contentious issue. Author describe our observations with the closure of hernial defect in LVHR in comparison to non-closure of defects in relation to seroma, pain, ileus, and recurrence. Methods: An observational study of closure versus non-closure of hernial defect in laparoscopic ventral hernia mesh repair was conducted in 81 patients from March 2016 to March 2017. Ventral hernia repair with mesh was done without closure of defect in 32 cases as compared to 49 cases in which closure of defect was done. Results: Seroma, pain, ileus and recurrence incidence are less in closure of defect in comparison to non-closure of defect in present study. Conclusions: With increasing experience, different theories and techniques have been described by different surgeons to overcome the intra operative and postoperative problems. During LVHR, closure of the hernial defect is a contentious issue. Closure of defect in the experience decreases rate of seroma formation. Closure of defect induce more post-operative pain but may be superior with regard to other important surgical outcomes. Duration of follow up is inadequate to conclude about incidence of recurrence in present study.